Job Stress and Teachers’ Coping Strategies in Nigerian Schools - Tayo, Subair, S.; Oluwaseun, Abe Olaitan; Olasunkanmi, Aliyu, M. (American Journal of Social Sciences and Humanities, 2021)
Stress is a natural part of everyday living thus, individuals experience varying levels of stress within and outside the work place but when in excess, stress results in loss of productivity. This study therefore examined whether Nigerian teachers experience stress on their job, assessed the extent to which stress affects their productivity and examined their coping strategies. These were with a view to providing information on level of job stress among Nigerian teachers, issues associated with it and the need to minimize job stress among teachers. The study adopted descriptive survey research method. The population for the study was 6,982 while 270 teachers purposively selected constituted the sample frame. A self-designed instrument: Job Stress and Teachers’ Coping Strategies Questionnaire (JSCS-Q) was used for data collection with percentage to answer the research questions. The results showed that having to teach very large classes (92.2%), marking and recording for all the students in such classes (88.1%) constituted stress for teachers. Others include; gross inadequate instructional materials (93.3%), poor conditions of service (87.5%), heavy workload (83.7%), students’ indiscipline and people’s attitude towards teachers (80.4%). Consequently, all of these caused Nigerian teachers’ productivity to be affected to a very large extent. Also, Nigerian teachers had to cope by chatting with colleagues (82.6%), physical exercising (78.9%), relaxation and behavioural modifications (72.2%) and (71.1%) respectively. This study concluded that teaching job has stress and teachers devise coping strategies themselves.